A tangled threesome: understanding arbovirus infection in Aedes spp. and the effect of the mosquito microbiota - Mantilla-Granados, Juan S.; Castellanos, Jaime E.; Velandia-Romero, Myriam Lucía (Frontiers in Microbiology, 2024)
Arboviral infections transmitted by Aedes spp. mosquitoes are a major threat to human health, particularly in tropical regions but are expanding to temperate regions. The ability of Aedes aegypti and Aedes albopictus to transmit multiple arboviruses involves a complex relationship between mosquitoes and the virus, with recent discoveries shedding light on it. Furthermore, this relationship is not solely between mosquitoes and arboviruses, but also involves the mosquito microbiome. Here, we aimed to construct a comprehensive review of the latest information about the arbovirus infection process in A. aegypti and A. albopictus, the source of mosquito microbiota, and its interaction with the arbovirus infection process, in terms of its implications for vectorial competence. First, we summarized studies showing a new mechanism for arbovirus infection at the cellular level, recently described innate immunological pathways, and the mechanism of adaptive response in mosquitoes. Second, we addressed the general sources of the Aedes mosquito microbiota (bacteria, fungi, and viruses) during their life cycle, and the geographical reports of the most common microbiota in adults mosquitoes. How the microbiota interacts directly or indirectly with arbovirus transmission, thereby modifying vectorial competence. We highlight the complexity of this tripartite relationship, influenced by intrinsic and extrinsic conditions at different geographical scales, with many gaps to fill and promising directions for developing strategies to control arbovirus transmission and to gain a better understanding of vectorial competence. The interactions between mosquitoes, arboviruses and their associated microbiota are yet to be investigated in depth.